Prevalence and Determinants of Virological Non-Suppression Among HIV Infected Adolescents on Antiretroviral Treatment At Kanyama General Hospital, Lusaka, Zambia - Siameka, Daniel; Muyoyeta, Monde; Kaonga, Patrick (Insights in Public Health Journal, 2024)
Background Zambia continues to face challenges in addressing the HIV epidemic among adolescents. Despite implementing various interventions to improve viral suppression among adolescents, the proportion of adolescents achieving viral load (VL) suppression remains low compared to the adults, and below the Joint United Nations Programme on HIV/AIDS (UNAIDS) 95% target. Therefore, the study estimated the proportion and determined the factors associated with non-suppression among HIV infected adolescents on antiretroviral treatment at Kanyama General Hospital, Lusaka, Zambia Methods A cross-sectional study was conducted using routinely collected data from SmartCare on adolescents (10 – 19 years) receiving ART for the period 1st January 2020 to 30th September 2022. Demographic and clinic characteristics data was extracted. The study defined virological non-suppression as having VL count ≥1000 RNA copies/mL. The study used multivariable logistic regression to identify factors associated with virological non-suppression. Data analysis was conducted in Stata 14. Results Of the 415 study participants, majority were 15-19 years (62.4%, 259/415) were female (56.6%, 235/415). The proportion of non-suppression was 5.8% (24/415, 95% CI=0.04-0.08). Age and sex showed no significant association with virological non-suppression, indicated by p-values of 0.089 and 0.310, respectively. Both treatment duration on ART and current treatment line were identified as determinants of virological non-suppression, with treatment duration on ART showing slightly decreased odds of (AOR=0.99, 95% CI=0.98-1.00) and being on the 2nd treatment line/regimen was associated with increased odds (AOR=8.09, 95% CI=2.71-24.17) of virological non-suppression. Conclusion The study found a prevalence of 5.8% virological non-suppression among adolescents. Treatment duration on ART and 2nd treatment line/regimen were found as determinants of virological non-suppression. Need to continuously monitor adolescent’s treatment duration on ART to avoid them moving 2nd treatment line/regimen.